Screening and characterization of natural extracts as dual-functional regulators for cardiomyocyte regeneration and cardiac repair - Liu, Jianfeng; Kuang, Chunyan (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveCardiovascular diseases (CVDs), the leading cause of global mortality, demand novel strategies to enhance cardiac regeneration. While ongoing research has begun to address the critical need for novel therapies aimed at regenerating cardiomyocytes in the context of cardiovascular disease, existing pharmacological interventions remain insufficient. This study was designed to systematically evaluate natural extracts for their potential to enhance cardiomyocyte differentiation and facilitate cardiac repair.MethodsWe performed an extensive literature review and identified 22 natural extracts associated with cardiac regeneration and stem cell differentiation. Through the use of a Tnnt2H2B-mCherry reporter mouse embryonic stem cell (mESC) line, we determined that Ganoderma lucidum water extract (GLW) are potent inducers of cardiomyocyte differentiation both in vivo and in vitro.ResultsGLW extracts significantly increased the proportion of beating cardiomyocytes, upregulated cardiac-specific markers (e.g., Tnnt2, Myh6), and enhanced the expression of key transcription factors (Isl1, Nkx2.5, Gata4, Mef2c) during cardiac progenitor cell (CPC) specification. Mechanistically, GLW modulated the Wnt signaling pathway, which is critical for CPCs specification. in vivo research experiments have shown that GLW can treat mice with myocardial infarction (MI) and improve cardiac function,as evidenced by increased ejection fraction and fractional shortening, along with enhanced proliferation of cardiomyocytes. Notably, GLW, particularly at higher doses, and promoted structural maturation of cardiomyocytes.ConclusionsOur findings underscore the potential of GLW as promising candidates for dual-functional therapies targeting myocardial regeneration and injury mitigation, providing novel insights into natural product-based interventions for CVD management.